Idaho State Building, Alaska-Yukon-Pacific-Exposition, Seattle, Washington, 1909 - University of Washington Libraries. Special Collections Division (1909)
Caption on image: Idaho Building. A.Y.P.E. 1171. Oakes Photo Co. PH Coll 777 Oakes.1171 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number